Heat stress exposure changed liver lipid metabolism and abdominal fat deposition in broilers. Issue 1 (31st December 2022) - Lan, Ruixia; Wang, Yuchen; Wei, Linlin; Wu, Fan; Yin, Fuquan
Abstract: To evaluate the effects of heat stress on lipid metabolism in the liver and abdominal adipose deposition in broilers, totally, 120 female 21-day old broilers were selected and randomly allocated to 2 groups with 6 replication and 10 broilers per each replication. Broilers in the control group (CON) were reared at 24 °C, and broilers in the heat stress group (HS) were reared at 34 °C. Heat stress exposure increased ( P < 0.05) rectal temperature, relative weight of abdominal adipose and liver, serum triacylglycerol (TG) and total cholesterol (TC) level, liver TG, TC, and very low-density lipoprotein (VLDL) content. Hepatic mRNA expression level of fatty acid synthase ( FAS ), acetyl-coenzyme A carboxylase ( ACC ), and abdominal adipose mRNA expression level of ACC and CCAAT/enhancer-binding protein-α ( C/EBPα ) were up-regulated ( P < 0.05) when compared with the CON group. Heat stress exposure increased serum and hepatic TC and TG content, up-regulated the mRNA expression of FAS and ACC in liver, and promoted preadipocytes differentiation by increasing C/EBPα mRNA expression in abdominal adipose. Therefore, heat stress exposure increased abdominal adipose deposition, which related to increase in hepatic de novo lipogenesis, and promoted preadipocytes differentiation in abdominal adipose. HIGHLIGHTS: Heat stress increased abdominal adipose deposition Heat stress increased hepatic de novo lipogenesis Heat stress promoted preadipocytes differentiation in abdominal adipose